Exosome Mimetics-Loaded Hydrogel Accelerates Wound Repair by Transferring Functional Mitochondrial Proteins - Zhu, Jie; Liu, Zhixiao; Wang, Ling; Jin, Qishu; Zhao, Yunpeng; Du, Antong; Ding, Neng; Wang, Yue; Jiang, Hua; Zhu, Lie (Frontiers in Bioengineering and Biotechnology, 2022)
Loading Mesenchymal stem cells (MSCs) derived exosomes on hydrogel scaffold developed a strategy for rapid wound healing. The clinical application of exosomes is hindered by low production, and exosome mimetics could be substitutable for exosomes. Here, the therapeutic effects of exosomes loaded hydrogel and exosomes mimetics loaded hydrogel on wounds are evaluated. Our results revealed that exosomes mimetics loaded hydrogel surprisingly promotes wound healing more efficiently than exosomes. Exosome mimetics can promote the proliferation and migration of dermal fibroblasts (hDF-a) more than exosomes in vitro. To investigate how exosome mimetic play it roles, proteomics analysis was applied, and the results suggest that exosomes mimetics significantly overexpress mitochondrial-derived oxidative phosphorylation-related proteins in comparison to exosomes. Overall, our work envisages the emerging potential of exosome mimetics, which take advantage of naturally sorted exosomes and broaden or enhances the inherent therapeutic capability. MSC-derived exosomes mimetics loaded hydrogel has a remarkable prospect for clinical application.